What to Expect When Expecting With Systemic Lupus Erythematosus (SLE): A Population‐Based Study of Maternal and Fetal Outcomes in SLE and Pre‐SLE. Issue 7 (July 2016) - Arkema, Elizabeth V.; Palmsten, Kristin; Sjöwall, Christopher; Svenungsson, Elisabet; Salmon, Jane E.; Simard, Julia F.
Abstract : Objective: To assess maternal and fetal outcomes associated with subclinical (pre‐systemic lupus erythematosus [SLE] and SLE presenting up to 5 years postpartum) and prevalent maternal SLE during pregnancy compared with the general population. Methods: This prospective cohort study used population‐based Swedish registers to identify 13, 598 women with first singleton pregnancies registered in the Medical Birth Register (551 prevalent SLE, 65 pre‐SLE within 0–2 years, 133 pre‐SLE within 2–5 years, and 12, 847 general population). SLE was defined as ≥2 SLE‐coded discharge diagnoses in the patient register with ≥1 diagnosis from a specialist. Unadjusted risks of adverse pregnancy or birth outcomes were calculated by SLE status, and Cochran‐Armitage tests evaluated trend across exposure groups. Results: Maternal outcomes such as preeclampsia, hypothyroidism, stroke, and infection were more common among women with SLE. Sixteen percent of prevalent‐SLE pregnancies were diagnosed with preeclampsia compared with 5% of those from the general population. Among the pre‐SLE women, preeclampsia was found in 26% of those with SLE within 2 years postpartum and 13% in those with SLE within 2–5 years postpartum. Similarly, infant outcomes, such as preterm birth, infection, and mortality, were worse among those born to mothers with prevalent SLE and pre‐SLE during pregnancy. The test for trend was significant for most outcomes. Conclusion: Our data demonstrate that adverse maternal and fetal outcomes are more common in SLE pregnancies. Furthermore, these unfavorable outcomes are observed in pregnancies occurring prior to the diagnosis of SLE. Thus, the underlying immunologic profile of SLE and alterations preceding clinical SLE may contribute to these pregnancy complications.